CT-SCAN ABDOMEN EXAMINATION TECHNIQUE IN CASES OF INTRA-ABDOMEN TUMORS AT THE AULIA HOSPITAL RADIOLOGY INSTALLATION - Alvin Khoiri; Gusti Rahmita (Medical Imaging and Radiation Protection Research Journal, 2023)
Background: CT scans can be used as a supporting tool to evaluate various abnormalities and determine certain clinical conditions, one of which is abdominal examination to make clinical diagnoses such as intra abdominal tumors. In this article, an abdominal CT-Scan examination procedure has been carried out in cases of intra-abdominal tumors at the Aulia Hospital Radiology installation. This study aims to determine the abdominal CT-Scan examination procedure in cases of intra-abdominal tumors and to find out information on abdominal CT scans in cases of intra-abdominal tumors at the Aulia Hospital Radiology Installation. Method: The type of research used in this research is qualitative research with a case study approach. Results: The results of the study show that abdominal CT scans in cases of intra-abdominal tumors at the Aulia Hospital installation can be carried out without contrast and the patient is positioned head first. Conclusion: CT scan diagnostic information in cases of plain intra-abdominal tumors is able to provide indications. However, it is better to do an examination with contrast media.